Estudos hidrológicos para capacidade de reservatórios - Dominguez, Carlos Rodrigo Zeas (1977)
In this work, a survey was made an hidrological studies dealing with capacity estimates of reservoirs. A classification of methodologies was used by dividing the subject into three groups: empirical, experimental and analitical. Techniques pertening to each group were selected, being studied, analysed and applied to specific cases with different regulating values (considered as percentages of the means), which are the following: a) Low flow techniques and sequent peak algorithms (empirical methodologies); b)Sequent peak algorithms applied to series generated and adjusted to theorical distribution frequencies of the Pearson family (experimental methodology); and, c)Dam theory (Moran) and deficit analysis (analitical methodologies). The applications were made for the river basins of São Francisco and Iguaçu located at Três Marias and Salto Osorio, respectively. The results of each technique is presented and discussed.